Two Highly Stable Silver Nanoparticles: Surface Plasmon Resonance Spectra Study of Silver Nanoparticles Capped with m-Hydroxybenzoic Acid and p-Hydroxybenzoic Acid - Gusrizal Gusrizal; Sri Juari Santosa; Eko Sri Kunarti; Bambang Rusdiarso (Universitas Jenderal Soedirman, 2018)
Silver nanoparticles capped with m-hydroxybenzoic acid and p-hydroxybenzoic have been successfully synthesized, but the long-term stability data of these silver nanoparticles are not available. In this paper, we report the stability of these two types of silver nanoparticles for a period of 40 weeks observation based on the change of surface plasmon resonance spectra of silver nanoparticles. Silver nanoparticles were synthesized by reduction of silver nitrate with m-hydroxybenzoic acid and p-hydroxybenzoic acid without addition of capping agent. The presence of silver nanoparticles was indicated by the appearance of yellow color due to the surface plasmon resonance of silver nanoparticles. The resulted silver nanoparticles were stored at room temperature and further UV-visible spectrophotometer was used to follow the change in surface plasmon resonance spectra. The surface plasmon resonance spectra of silver nanoparticles were overlapped for the first 18 weeks, followed by little change in the position of absorption maxima (lmax), peak intensity, and width of the absorption peak until the week of 40. Silver nanoparticles capped with m-hydroxybenzoic acid and silver nanoparticles capped with p-hydroxybenzoic acid were highly stable which should make them suitable for further applications. The results show the potential of m-hydroxybenzoic acid and p-hydroxybenzoic acid to become a new reducing agent in the synthesis of highly stable silver nanoparticles. The m-hydroxybenzoic acid and p-hydroxybenzoic acid appeared to act as both reducing and capping agent.